A new route for preparation of sodium-silicate-based hydrophobic silica aerogels via ambient-pressure drying - Bangi, Uzma K H (Sci Technol Adv Mater, 2008)
An in-depth investigation into the synthesis of hydrophobic silica aerogels prepared by the surface derivatization of wet gels followed by subsequent drying at ambient pressure is reported. The following sol–gel parameters were examined for their effect on the physical properties of the derived aerogels: number of gel washings with water, percentage of hexane or methanol in silylating mixture, molar ratio of tartaric acid: Na(2)SiO(3), gel aging period, weight% of silica, trimethylchlorosilane (TMCS) percentage, and silylation period. These parameters were varied from 1 to 4, 0 to 100%, 0.27 to 1.2, 0 to 4 h, 1.5 to 8 wt.%, 20 to 40% and 6 to 24 h, respectively. The properties of hydrophobic silica aerogels synthesized by this new route were investigated in terms of bulk density, percentage volume shrinkage, percentage porosity, thermal conductivity and contact angle with water, and by Fourier transform infrared spectroscopy (FTIR). The as-prepared hydrophobic silica aerogels exhibited high temperature stability (up to approximately 435 °C) as measured by thermogravimetric/differential thermal analysis (TGA-DTA). The optimal sol-gel parameters were found to be a molar ratio of Na(2)SiO(3):H(2)O : tartaric acid : TMCS of 1 : 146.67 : 0.86 : 9.46, an aging period of 3 h, four washings with water in 24 h and the use of a 50% hexane- or methanol-based silylating mixture. Aerogels prepared with these optimal parameters were found to exhibit 50% optical transparency in the visible range, 84 kg m(−3) density, 0.090 W mK(−1) thermal conductivity, 95% porosity and a contact angle of 146° with water.